Progressive Nature of Social and Economic Rights in Kenya: a Delayed Promise? - Jennifer Gitiri (Constitutional Review, 2020)
This paper evaluates the steps taken towards the progressive realization of social and economic rights (SER) in Kenya. It aims to provide a better understanding of SER and the obligations of the state under international, regional, and national law. It further elucidates the components of progressive realization. Additionally, it identifies the guiding principles of measuring progressive realization and recommendations to develop tools that would monitor progressive realization. Recognition of SER faces many challenges as they are considered as second class rights that are not equal to civil and political rights considered as first-generation rights. The most enduring challenge for SER is that it interferes with the concept of the separation of powers and the political question doctrine by enabling courts to interfere in matters considered to be under the purview of the legislative and executive branch. The paper uses a desktop review of international, regional, and national legal instruments as well as comparative evaluation of SER jurisprudence from a host of jurisdictions. The concept of progressive realization is a goal in the ICSECR, Kenya’s Constitution, and other Constitutions with the implication that SER would be implemented over a period of time. Jurisprudence from other jurisdictions is evaluated to determine the lessons learned by Kenya. The paper demonstrates that progressive realization and implementation of SER are still work in progress before they are finally anchored into mainstream human rights, just like political and civic rights. In conclusion, progressive realization of SER imports an immediate obligation by Kenya having ratified the three human right bodies (ICSECR, UNCRC, and CRPWD) pursuant to Article 2(5)(6) of the Constitution to expeditiously move towards the realization of SER. There is a further presumption that the country would refrain from retrogressive measures and instead adopt the minimum content approach in the implementation of SER.